Penyuluhan Pengaruh Negatif Rokok Bagi Kesehatan Remaja Serta Hukum Rokok Menurut Hukum Positif dan Hukum Islam - Mohamad Kharis Umardani; Ahmad Ronal; Johan Satria Putra (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2019)
Smoking is a cause of premature death because it can endanger health and become the first entrance to other negative behaviors and early know Narcotics. The temptation to smoke in adolescents is associated with affective states and nicotine withdrawal symptoms making it difficult to quit smoking. Therefore, there should be an effort to stop it. While cigarettes contain thousands of toxins that have been medically proven to damage and endanger health. Even kill its users slowly, but God has said:وَلَا تَقْتُلُوا أَنْفُسَكُمْ إِنَّ اللَّهَ كَانَ بِكُمْ رَحِيمًا“And do not kill yourself; Allah is Most Merciful to you” (Surat an-Nisaa:2)